(3GdYOGdI GdJfXjejI (B:s (3GdegeI GdbGOeI dEOGQI GdehGQO GdHTQjI (B/s - (3RGjO, YGOd eMeOs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2006)
(3GdEWGQ GdeaGgjej ddYOGdI GdJfXjejI(B- (3GdeOGNd GdEOGQjI ddYOGdI GdJfXjejI(B- (3GdKbGaI GdJfXjejI hGdYOGdI(B- (3GdYhGed GdHjFjI hCKQgG Ydi GdYOGdI GdJfXjejI(B- (3HQfGeL GdNUNUI hGdJbdU GdJfXjej(B- (3OhQ EOGQI GdehGQO GdHTQjI aj JMbjb GdYOGdI(B- (3GdeQCI GdYGedI hGdYOGdI hGdSdhc GdJfXjej(B- (3JMbjb GdYOGdI HGSJNOGe feGPL GdLOGQI(B- (3MGdI GdYOGdI aj Hfc GdJbOe(B.s
Keywords: (3EOGQI GdehGQO GdHTQjIs; (3GdJfXjes